To solve the given equation \( i(z + 3) = 5 \), let's fill in the blanks for each step.
Step 1: \((i) (z + 3) = 5 \Rightarrow (i) = 1/4\).
Step 2: \(z + 3 = \frac{5}{i}\).
Step 3: Subtract \([3]\) from both sides.
Step 4: \(z = \frac{5}{i} - 3\).
Step 5: \(\frac{2}{i} = | \).
This interpretation assumes that the problem was to solve for \( z \) in the equation provided. Note that steps may vary based on your definitions, especially whether \( i \) indicates the imaginary unit. You can further simplify the problem if needed using specific values for \( i \).